2019
DOI: 10.1146/annurev-pathmechdis-012418-012818
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Pathogenic Interactions Among Environment, Host, and Tumor at the Crossroads of Molecular Pathology and Epidemiology

Abstract: Evidence indicates that diet, nutrition, lifestyle, the environment, the microbiome, and other exogenous factors have pathogenic roles and also influence the genome, epigenome, transcriptome, proteome, and metabolome of tumor and nonneoplastic cells, including immune cells. With the need for big-data research, pathology must transform to integrate data science fields, including epidemiology, biostatistics, and bioinformatics. The research framework of molecular pathological epidemiology (MPE) demonstrates the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
143
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 186 publications
(149 citation statements)
references
References 157 publications
(172 reference statements)
1
143
0
Order By: Relevance
“…Recent technological advances are enabling the development of emerging research fields such as the Molecular Pathological Epidemiology (MPE) incorporating interpersonal heterogeneity of a disease process into epidemiology (Hamada, Keum, Nishihara, & Ogino, ). In this framework the integration of data capturing the complex combination of genetic heterogeneity (endogenous factors) and the environment (exogenous factors) is providing novel insights underlying etiologic mechanisms of different cancer types (Ogino, Nowak, Hamada, Milner Jr, & Nishihara, ) and define new therapeutic strategies (Ogino et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Recent technological advances are enabling the development of emerging research fields such as the Molecular Pathological Epidemiology (MPE) incorporating interpersonal heterogeneity of a disease process into epidemiology (Hamada, Keum, Nishihara, & Ogino, ). In this framework the integration of data capturing the complex combination of genetic heterogeneity (endogenous factors) and the environment (exogenous factors) is providing novel insights underlying etiologic mechanisms of different cancer types (Ogino, Nowak, Hamada, Milner Jr, & Nishihara, ) and define new therapeutic strategies (Ogino et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Intake of dietary calcium, dairy calcium, and calcium supplement and risk of colorectal cancer according to densities of tumor-infiltrating T-cell subsets in the NHS the cohorts. The integration of tumor immunology analyses into the framework of molecular pathologic epidemiology is an emerging research area (49,50), which enabled us to better understand etiologic heterogeneity according to tumor molecular and immune features. However, several limitations should be noted.…”
Section: Discussionmentioning
confidence: 99%
“…An MPE study was conducted to test this association and found that a diet rich in fiber and whole grains was associated with a decreased risk of colorectal cancer in persons containing F. nucleatum, suggesting decreased carcinogenesis through suppression of this microorganism. Further MPE studies on pathogenic interactions between the environment, immune system and tumor cells will shed light upon the mechanisms of the effect of ecosystem disruption on human immune system dysfunction and other epigenetic modification of our body, which in turn contributes to tumorigenesis [15,16].…”
Section: Ecosystem and Cancermentioning
confidence: 99%